Ototoxic Adverse Drug Reactions: A Disproportionality Analysis Using the Italian Spontaneous Reporting Database - Barbieri, Maria Antonietta; Cicala, Giuseppe; Cutroneo, Paola Maria; Mocciaro, Eleonora; Sottosanti, Laura; Freni, Francesco; Galletti, Francesco; Arcoraci, Vincenzo; Spina, Edoardo (Frontiers in Pharmacology, 2019)
Introduction: The panorama of drug-induced ototoxicity has widened in the last decades, moreover, post-marketing data are necessary to gain a better insight of ototoxic Adverse Drug Reactions (ADRs). The aim of this study was to perform an analysis of ADR reports describing drug-induced ototoxicity from the Italian Spontaneous Reporting System (SRS). Methods: As a measure of disproportionality, we calculated the Reporting Odds Ratios (RORs) and 95% Confidence Intervals (CIs) with a case/non-case methodology. Cases were all suspected ADR reports regarding drug-induced ototoxicity collected into the Italian SRS from 2001 to 2017. Non-cases included all other ADRs reported in the same period. Results: Of 325.980 reports, 652 included at least one ototoxic ADR, compared with 325.328 non-cases. Statistically significant adjusted RORs were found for drugs for cardiovascular disorders, urologicals, teriparatide, amikacin, prulifloxacin, rifampicin and isoniazid, cisplatin, hormone antagonists, tacrolimus, pomalidomide, tramadol and antidepressants. Significant adjusted RORs in relation to tinnitus were also observed for doxazosin (ROR 5.55, 95% CI 2.06-14.93), bisoprolol (4.28, 1.59-11.53), nebivolol (8.06, 3.32-19.56), ramipril (3.96, 2.17-7.23), irbesartan (19.60, 9.19-41.80), betamethasone (4.01, 1.28-12.52), moxifloxacin (4.56, 1.71-12.34), ethambutol (12.25, 3.89-38.57), efavirenz (16.82, 5.34-52.96), sofosbuvir/ledipasvir (5.95, 1.90-18.61), etoposide (7.09, 2.63-19.12), abatacept (6.51, 2.42-17.53), indometacin (6.30, 2.02-19.72), etoricoxib (5.00, 2.23-11.23), tapentadol (4.37, 1.09-17.62) and timolol, combinations (23.29, 9.53-56.95). Moreover, significant adjusted RORs for hypoacusis regarded clarithromycin (3.95, 1.86-8.40), azithromycin (10.23, 5.03-20.79), vancomycin (6.72, 2.14-21.11), methotrexate (3.13, 1.00-9.81), pemetrexed (4.38, 1.40-13.76), vincristine (5.93, 1.88-18.70), vinorelbine (21.60, 8.83-52.82), paclitaxel (2.34, 1.03-5.30), rituximab (3.20, 1.19-8.63), interferon alfa-2b (17.44, 8.56-35.53), thalidomide (16.92, 6.92-41.38) and deferasirox (41.06, 20.07-84.01). Conclusions: This study is largely consistent with results from literature. Nevertheless, propafenone, antituberculars, hormone antagonists, teriparatide, tramadol and pomalidomide are unknown of being ototoxic. Hypoacusis after the use of vinorelbine, methotrexate and pemetrexed is unexpected such as tinnitus related with etoposide, nebivolol, betamethasone, abatacept, sofosbuvir/ledipasvir and tapentadol, but these considerations require further investigation to better define the risk due to the paucity of data. Moreover, physicians should be aware of the clinical significance of ototoxicity and be conscious about the importance of their contribution to spontaneous reporting.